Barriers to uptake and implementation of malaria chemoprevention in school-aged children: a stakeholder engagement meeting report - Morlino, Colette; Byrne, Isabel; Achan, Jane; Baraka, Vito; Barry, Aissata; Bousema, Teun; Camara, Alioune; Chacky, Frank; Chico, R. Matthew; Clarke, Sian E.; Collins, Katharine A.; Dagnon, Seynude Jean-Fortune; et al. (Frontiers in Tropical Diseases, 2025)
Malaria is a leading cause of death in school-aged children in sub-Saharan Africa, and non-fatal chronic malaria infections are associated with anaemia, school absence and decreased learning, preventing children from reaching their full potential. Malaria chemoprevention has led to substantial reductions in malaria in younger children in sub-Saharan Africa. In 2022, the WHO updated its recommendations for chemoprevention to older, school-aged children where epidemiologically indicated. To date, there has been limited uptake of these policies which include both extending the age of seasonal malaria chemoprevention in seasonal transmission settings and providing intermittent preventive treatment to school-aged children in perennial transmission settings. In April 2024, a stakeholder meeting was convened in Kigali, Rwanda, to analyse barriers to implementation of malaria chemoprevention targeting school-aged children. Key evidence gaps were identified and needs for coordination and advocacy were highlighted.